Nitric oxide as prediction factor of gingival inflammation in orthodontic patients - Janošević Predrag; Stojanović Ivana; Janošević Mirjana; Filipović Gordana; Stošić Maja (Vojnosanitetski Pregled)
Background/Aim. Nowadays therapy with fixed orthodontic appliances is widely spread, having in mind positive effects it has in malocclusion treatments The side effect is increased gingivial inflammation in treated patients. The aims of this research are to estimate the inflammatory condition of gingiva in the first 6 months of orthodontic therapy on the basis of clinical parameters of sulcus bleeding index, plaque index, gingival crevicular fluid and salivary nitric oxide concentration, and to investigate role of nitric oxide as predicting factor of gingival inflammation in orthodontic patients. Methods. In this study, 30 patients of the Dental Clinic treated with fixed orthodontic appliances (11 males and 19 females), aged 15-22 years, were examined. Clinical parameters were evaluated and gingival crevicular fluid and saliva were collected, before the beginning of orthodontics therapy, and then, three and six months after it. Results. The approximate values of clinical parameters, gingival crevicular fluid and salivary nitric oxide concentration progressively increased. Low statistical significance of correlations among gingival crevicular fluid and salivary nitric oxide concentration and the measured clinical parameters were found. There is a statistically significant correlation between gingival crevicular fluid and salivary nitric oxide concentration. Conclusion. According to the obtained results, we can conclude that gingival crevicular fluid and saliva are reliable mediums for monitoring of the gingival inflammatory condition. More studies are needed to investigate a potential role of nitric oxide as predicting factor of gingival inflammation in orthodontic patients.